Application of the Valsalva maneuver in medicine and sport - Karkos, Patrycja; Kuśmierczyk, Katarzyna; Jurga, Marta; Gastoł, Bartłomiej; Mikołap, Karolina; Kras, Marta; Staroń, Arkadiusz; Sztemberg, Elena; Plizga, Jakub; Głuszczyk, Agnieszka (Quality in Sport, 2024)
The Valsalva maneuver, named after Antonio Maria Valsalva, is one of the vagal maneuvers. It is defined as a forced expiration against a closed glottis, leading to an increase in intrathoracic and intra-abdominal pressure. Over the years it has become a subject of interest to many clinical researchers who have comprehensively studied its physiology and clinical significance. As a result, the application of the Valsalva maneuver has expanded to become a versatile technique applied across a wide range of medical specialties as a diagnostic and therapeutic tool. Additionally, it has found its use in sport among athletes. The aim of this article is to present the current state of knowledge about the clinical significance of the Valsalva maneuver and show that this simple physiological technique described in the 18th century remains a valuable tool in modern clinical practice and has found its use in sport. The review was based on chosen literature obtained from the PubMed electronic database, Google Scholar electronic database, and other scientific articles. Search terms included keywords listed below. Keywords: Valsalva maneuver; vagal maneuver; respiratory maneuver; autonomic system